MENINGKATKAN LITERASI MELALUI LOMBA MEMBACA PUISI DI MADRASAH IBTIDAIYAH DARUSSALAM DESA BUNGO TANJUNG - Lussy Rahmadani; Sri Utaminingsih (AbdiMasya | Hira Institute, 2023)
There is no in-depth poetry teaching at MI-Darusslam Bungo Tanjung Village. This has an impact on the knowledge that students have regarding poetry reading techniques. held a poetry reading competition aimed at exploring and developing the potential of MI-Darussalam students. This activity aims to provide poetry reading training for MI-Darussalam students in Bungo Tanjung Village by implementing poetry reading techniques for students, so that students are expected to know about poetry and be able to read poetry well. The method used is the method of presenting material and mentoring so that the results are as expected. Based on the implementation of the poetry reading training activity for MI-Darussalam students in Bungo Tanjung Village which was carried out well and smoothly, it can be concluded as follows: first, this activity produced new knowledge for the students about poetry, especially poetry reading techniques. Second, students acquire various poetry reading teachniques such as vowels, pauses, intonation, expression and appreciattion.